Tension‐free vaginal mesh surgery versus laparoscopic sacrocolpopexy for pelvic organ prolapse: Analysis of perioperative outcomes using a Japanese national inpatient database. (5th May 2018) - Obinata, Daisuke; Sugihara, Toru; Yasunaga, Hideo; Mochida, Junichi; Yamaguchi, Kenya; Murata, Yasutaka; Yoshizawa, Tsuyoshi; Matsui, Tsuyoshi; Matsui, Hiroki; Sasabuchi, Yusuke; Fujimura, Tetsuya; Homma, Yukio; et al.
Abstract : Objective: To compare nationwide outcomes of tension‐free vaginal mesh surgery and laparoscopic sacrocolpopexy for the treatment of pelvic organ prolapse in Japan. Methods: Using the Diagnosis Procedure Combination database, we collected data on female patients who underwent tension‐free vaginal mesh surgery or laparoscopic sacrocolpopexy for pelvic organ prolapse from April 2014 to March 2015. We compared the proportion of perioperative adverse events, duration of anesthesia, total costs and postoperative length of stay between the groups. Univariate and multivariate analyses were carried out for age, comorbidity, mesh volume, additional concomitant surgery and hospital volume. Results: We identified 3023 patients, including 2388 who underwent tension‐free vaginal mesh surgery, and 635 who underwent laparoscopic sacrocolpopexy. The median age at the time of surgery was significantly higher in the tension‐free vaginal mesh group (71 vs 66 years; P < 0.001). The tension‐free vaginal mesh group had a higher proportion of all adverse events (7.1% vs 1.8%; P < 0.001) and a higher proportion of genitourinary complications (5.7% vs 1.1%; P < 0.001). The median duration of anesthesia was shorter in the tension‐free vaginal mesh group (150 vs 286 min; P < 0.001). The total cost was significantly lower in the tension‐free vaginal mesh group. Conclusions: Both procedures offer favorable results for surgical treatment of pelvic organ prolapse. Overall, the tension‐free vaginal mesh procedure seems to represent a good option for high‐risk women, such as elderly patients, whereas laparoscopic sacrocolpopexy is useful for younger patients with a higher level of sexual activity.